(untitled) (Per Musi, 2021)
This study sought to understand how the sociocultural and socioeconomic contexts influences/ interferes/modifies the teacher development process of the music teachers who participated in this research, in the light of the perspective of gift, by Marcel Mauss. Following a qualitative methodology, we opted for the narrative interview, a dynamic method that is based on the pedagogical practice of educators. As a result of this study, we have reached the conclusion that there are diverse dimensions of musical education where the interviewees defend a sensitive listening to their own path, conceiving a pedagogical path guided by alterity and gift.